Naissus: A Review of Political and Economic Circumstances in the City from the 1st to the 5th Century - Ljubomirović, Irena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper is the result of the research of the history of ancient Naissus. Its aim is to present the history of Naissus in the ancient time when the city was a part of the Roman Empire. The research is based on literary and epigraphic sources and archaeological finds. The territory of Naissus was a part of two provinces, Dacia Mediterranea and Dacia Ripensis. Since Naissus was an ordinary provincial city, ancient writers of that time did not show much interest in its history. Thus, information on Naissus in literary sources is quite scarce and occasionally inaccurate. Some information on Naissus is found in the work of Procopius (De aedificiis), the document Notitia dignitatum, recording a workshop for making weapons and military equipment. Naissus also appears in the Theodosian Code, as one of the numerous towns where the emperors issused edicts and laws. Epigraphic monuments are of particular importance for studying the history of any Roman city. These provide valuable information on the way of life, customs, religion, government, and military and social organization of the ancient world. Besides literary and epigraphic sources, the archaeological finds—remains of ancient buildings, temples, roads, bridges, objects of material culture, weapons, tools, jewellery—all contributed significantly to shedding light on the past of the city of Niš.